Of lions, Arabs & Israelites some lessons from the Samson story for writing the history of biblical scholarship - Kurtz, Paul Michael 1984- (2018)
This short essay follows a thread of evidence employed across many languages and lands, genres and generations to defend the historicity of the Samson story. Based upon this line of interpretation it stresses some necessary lessons for scholars writing the history of biblical scholarship. The inquiry extends beyond an interest in modern history to show the relevance of the history of scholarship for present research on ancient history and biblical literature.
Keywords: Historiography; history of scholarship; history of interpretation; Comparative Method